Solution-processed, highly crystalline, and oriented MAPbI₃ thin films by engineering crystal-growth kinetics - Ahmad, Riyas (2023)
Growing oriented and monocrystalline layers of lead halide perovskites over device substrates helps to harness their outstanding optoelectronic properties. Epitaxial growth of lead halide perovskites for device fabrication is limited by the lack of lattice-matched substrates and the requirement of compact pinhole-free films. Most optoelectronic devices use amorphous substrates, hindering oriented epitaxial growth. Here, we demonstrate highly crystalline methylammonium lead iodide (MAPbI3) thin films over amorphous substrates by meticulously optimizing the nucleation and growth kinetics in spin coating. The "epitaxial-like" films enable large-area crystalline layer fabrication, with larger than 100 μm spherulitic grains oriented along [200] and [224] planes. The compact, highly crystalline, and oriented films of MAPbI3 formed over ITO/SnO2 are used to fabricate perovskite solar cells (PSCs) with an area of 1 cm2. Despite the perovskite films being highly oriented and crystalline, the PSCs’ performances highlight the critical role the interfaces play in photovoltaic cells.